KEANDALAN EMBUNG LAMBADEUK UNTUK PEMENUHAN AIR BERSIH DI DAERAH PESISIR KECAMATAN PEUKAN BADA ACEH BESAR - Budi, Setia; Azmeri, Azmeri; Syamsidik, Syamsidik (JURNAL TEKNIK SIPIL, 2018)
Abstract : Water demand fulfillment in coastal area of Peukan Bada Sub District is still complicated. Peukan Bada Community in coastal area currently still depends on well water. The existence of Lambadeuk Small Dam located in Peukan Bada Sub District Aceh Besar, which River Flow Area (DAS) is 2.27 Km, is expected to be able in fulfilling clean water demand. The objectives of this research are to find out water supply, to optimize the operation and to obtain the reliability of Lambadeuk Small Dam Operation. The method used in operating the small dam is analyzed by Non Linear Program using Solver Microsoft Excel. In optimizing the operation, it is divided into three season conditions. The highest inflow discharge of dry season is in January which is 0.222 m3/sec or 0.594 MCM, while the highest inflow discharge of normal season is in December which is 0.294 m3/sec or 0.787 MCM, and the highest inflow discharge of wet season is in November which is 0. 463 m3/sec or 1.199 MCM. The projection of population and clean water demand for population need in coastal area of Peukan Bada Sub District can be described as for population 5,954 in 2015, the clean water demand is 0.0099 m3/sec so that in 2035, the population will become 10,534 and the clean water demand will be 0.0176 m3/sec. The average inflow from 2015 to 2035 for dry season is 4.031 MCM, for normal season is 5.816 MCM, and for wet season is 9.077 MCM. Water release is 0.312 MCM, and basic water demand is 0.556 MCM. Optimization reliability of Lambadeuk Small Dam Operation is reliable and 100% can fulfill the water demand in the downstream of the small dam, and the management organizer of Lambadeuk Small Dam can also expand service area of clean water demand in the coastal area of Peukan Bada Sub District Aceh Besar.Abstrak: Dalam pemenuhan kebutuhan air bersih di daerah pesisir Kecamatan Peukan Bada masih kesulitan untuk kebutuhan air bersih. Selama ini masyarakat di daerah pesisir masih mengandalkan air sumur. Dengan adanya Embung Lambadeuk yang terletak di Kecamatan Peukan Bada Kabupaten Aceh Besar, yang mempunyai luas Daerah Aliran Sungai (DAS) 2,27 Km, mampu untuk pemenuhan kebutuhan air bersih. Tujuan dari penelitian ini untuk mengetahui ketersediaan air, mengoptimalkan pengopersian dan mendapatkan keandalan pengopersian Embung Lambadeuk. Pada penelitian ini metode pengoperasian embung yang dianalisis menggunakan program Non Linear dengan solver Microsoft Excel. Dalam optimasi pengoperasian dikelompokan dalam tiga kondisi tahun musim, dimana kondisi tahun musim kering debit Inflow yang tertinggi berada pada bulan Januari sebesar 0,222 m3/dt dengan kapasitas 0,594 MCM, pada kondisi tahun normal debit yang tertinggi berada pada bulan Desember sebesar 0,294 m3/dt dengan kapasitas 0,787 MCM dan pada kondisi tahun basah debit yang tertinggi pada bulan Nopember sebesar 0,463 m3/dt dengan kapasitas 1,199 MCM. Proyeksi jumlah penduduk dan kebutuhan air bersih untuk pemenuhan penduduk di pesisir Kecmatan Peukan Bada, tahun 2015 dengan jumlah penduduk sebesar 5.954 jiwa, kebutuhan air bersih 0,0099 m3/dt dan Tahun 2035 jumlah penduduk sebesar 10.534 jiwa, kebutuhan air bersih 0,0176 m3/dt. Untuk Inflow tahun kering dari Tahun 2015 sampai Tahun 2035 Inflow rata-rata tahunan sebesar 4,031 MCM, tahun normal dari Tahun 2015 sampai tahun 2035 Inflow rata-rata sebesar 5,816 MCM, dan tahun basah Inflow rata-rata tahunan sebesar 9,077 MCM. Release air sebesar 0.312 MCM, dan kebutuhan air baku sebesar 0,556 MCM. Hasil yang dicapai adalah Pengoperasian Embung yang Optimal dan Keandalan Pengoperasian Embung. Dimana Keandalan Pengoperasian Embung Lambadeuk sangat berpengaruh dari volume dan periode waktu, dan terhadap Manajemen pengelola Embung Lambadeuk, bisa mengambil langkah-langkah untuk memperluas daerah layanan kebutuhan air bersih di pesisir Kecamatan Peukan Bada Aceh Besar.